PERAN KOMUNITAS SOSIAL DALAM PRAKTIK FILANTROPI MELALUI KEWIRAUSAHAAN SOSIAL (Studi kasus terhadap Organisasi Greeneration Foundation) - Febri Saefulloh Saefulloh; Yoga Gandara Gandara (Hermeneutika : Jurnal Hermeneutika, 2021)
Abstract This research has a background on social problems that occur in Indonesia. The problems that are often faced are not only in Indonesia but globally, starting from poverty, social inequality, unemployment, to individualistic behavior that does not care about the lives of fellow humans and the environment. This problem needs serious handling from all elements of society, including contributions from the social community. Greeneration Foundation is a social community formed from anxiety about human behavior that only cares about personal matters and does not pay attention to life in the future. Social entrepreneurship is a concrete philanthropic step carried out by this community. Through his programs and partnerships as the implementation of the vision of "green attitude green environment" he seeks to contribute through philanthropic practices that focus on improving people's attitudes and behavior to improve life and the environment. The research method uses qualitative with case studies. Data collection and processing techniques used observation, interviews, documentation studies, and triangulation. The results showed that the role of the social community in philanthropic practice by the Greeneration Foundation through ideas (Research) by observing and studying the environment and surrounding conditions, then realized by finding solutions to educate the community (Education) so that Greeneration Indonesia could take concrete actions (Actions) as well as campaigning. easy-to-implement solutions (Campaigns). through promoting a green lifestyle through tools (Tools) and systems (System), which are combined so that it is called the REACTS method. The results of entrepreneurship carried out through services and entrepreneurship are used as much as possible for social activities and empowering the surrounding community. Keywords: social community, philantrophy, greeneration foundation